Evaluating computing students' digital skills and health literacy: A case from Bulgaria - Kaloyanova, Kalinka; Leventi, Nikoleta; Kaloyanova, Elitsa (Frontiers in Public Health, 2023)
The main purpose of this article is to describe the importance and the challenges of digital health literacy as recognized during the COVID-19 pandemic. First, basic definitions of health literacy and digital health literacy are provided, followed by, and matched against digital competence frameworks, and health literacy skills content and scales. Based on that, a compatibility analysis is provided, against the expectations for satisfactory levels definition for the respective competences and skills. For the approbation of the approach, results received from the participation of computing students at the Sofia University St. Kliment Ohridski in the COVID-19 Health Literacy Survey are used.